Positioning: The Battle for Your Mind - Ries, Al and Trout, Jack (New Delhi McGraw Hill, 2015)
Positioning: The Battle For Your Mind is a business classic and provides readers expert, time-tested advice on advertising and branding.
Include Illustrations
Keywords: Advertising